Le vice de forme et le droit municipal - Rousseau, Gilles (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
How are administrative acts of local governments — as opposed to judicial and quasi judicial acts — affected by informality or, more generally speaking, by procedural irregularities ? The author ventures a few answers to the question in his analysis that spans from prerequisites to initial implementation